Methylprednisolone Treatment in Brain Death-Induced Lung Inflammation–A Dose Comparative Study in Rats - Van Zanden, Judith E.; ’T Hart, Nils A.; Ottens, Petra J.; Liu, Bo; Rebolledo, Rolando A.; Erasmus, Michiel E.; Leuvenink, Henri G. D. (Frontiers in Pharmacology, 2021)
Background: The process of brain death (BD) leads to a pro-inflammatory state of the donor lung, which deteriorates its quality. In an attempt to preserve lung quality, methylprednisolone is widely recommended in donor lung management. However, clinical treatment doses vary and the dose-effect relation of methylprednisolone on BD-induced lung inflammation remains unknown. The aim of this study was to investigate the effect of three different doses methylprednisolone on the BD-induced inflammatory response. Methods: BD was induced in rats by inflation of a Fogarty balloon catheter in the epidural space. After 60 minutes of BD, saline or methylprednisolone (low dose (5 mg/kg), intermediate dose (12.5 mg/kg) or high dose (22.5 mg/kg)) was administered intravenously. The lungs were procured and processed after 4 hours of BD. Inflammatory gene expressions were analyzed by RT-qPCR and influx of neutrophils and macrophages were quantified with immunohistochemical staining. Results: Methylprednisolone treatment reduced neutrophil chemotaxis as demonstrated by lower lower IL-8-like CINC-1 and E-selectin levels, which was most evident in rats treated with intermediate and high doses methylprednisolone. Macrophage chemotaxis was attenuated in all methylprednisolone treated rats, as corroborated by lower MCP-1 levels compared to saline treated rats. Thereby, all doses methylprednisolone reduced TNF-α, IL-6 and IL-1β tissue levels. In addition, intermediate and high doses methylprednisolone induced a protective anti-inflammatory response, as reflected by upregulated IL-10 expression when compared to saline treated brain-dead rats. Conclusion: We showed that intermediate and high doses methylprednisolone share most potential to target BD-induced lung inflammation in rats. Considering possible side effects of high doses methylprednisolone, we conclude from this study that an intermediate dose of 12.5 mg/kg methylprednisolone is the optimal treatment dose for BD-induced lung inflammation in rats, which reduces the pro-inflammatory state and additionally promotes a protective, anti-inflammatory response.